Routledge handbook of gender and feminist geographies - Datta, Anindita; Hopkins, Peter; Johnston, Lynda; Olson, Elizabeth; Silva, Joseli Maria (London Routledge, 2023)
This handbook provides a comprehensive analysis of contemporary gender and feminist geographies in an international and multi-disciplinary context. It features 48 new contributions from both experienced and emerging scholars, artists and activists who critically review and appraise current spatial politics. Each chapter advances the future development of feminist geography and gender studies, as well as empirical evidence of changing relationships between gender, power, place and space. Following an introduction by the Editors, the handbook presents original work organized into four parts which engage with relevant issues including violence, resistance, agency and desire.